Representación efectiva de dinámicas fisiológicas mediante fuzzy rough set: una revisión (2011)
The latest generation of biomedical systems record at short time intervals the physiological dynamic in large databases. The correct interpretation of the information is difficult to obtain by the expertise of a single physician, so the decision is based only on some selected variables. Effective representation of physiological variables by fuzzy Rough Set type 1 can be applied to characterize and extract relevant information from physiological dynamics, however the disadvantages of these techniques are the complexity of their algorithms and the high computational cost, therefore it is necessary to apply fuzzy rough set type 2 techniques , associated with axiomatic methods through low and high diffuse approximation operators as primitive concepts for generating a dimension reduction system with a tendency to lower computational cost in biomedical engineering applications. This article reviews the state of the art of effective representation of physiological dynamics using fuzzy rough set, in order to determine the ability of these techniques to be included in automatic decision making procedures that support the clinical opinion of a specialist.